Adsorption of Heavy Metals from Low Concentration Solutions onto Dried Chlamydomonas reinhardtii - Maria Giuseppina Genduso; Marianna Guagliano; Elisabetta Finocchio; Cinzia Cristiani; Giovanni Dotelli; Giulia Santomauro (Applied Sciences, 2024)
Heavy metals, such as Pb(II), Cr(III), and Cd(II), are frequently discharged into the environment, resulting in a threat for the health of living organisms. Microalgae represent an ecological method for the removal of these pollutants. The capture capability of active and dried Chlamydomonas reinhardtii towards both mono-ionic and multi-ionic solutions is evaluated to study the bioremediation in low-polluted wastewaters. Several characterization techniques have been performed to study morphology, composition, and the interaction between the metals and the microalgal functional groups of the wall. The effect of the operating conditions, such as contact time and pH, is assessed; an increased contact time of 4 days did not influence the adsorption yields of Pb and Cr, but it had a negative effect on Cd adsorption, while the impact of pH was mainly affecting the chemical speciation, rather than the adsorption capability. The microalga showed a larger affinity for Pb and Cd, respectively, 80 and 76% (w/w) of adsorption, while only the 65% (w/w) of the total Cr was adsorbed, suggesting a preferential biosorption.